Neovascular Age-Related Macular Degeneration (nAMD): A Review of Emerging Treatment Options - Tan CS; Ngo WK; Chay IW; Ting DS; Sadda SR (Clinical Ophthalmology, 2022)
Colin S Tan,1,2 Wei Kiong Ngo,1,2 Isaac W Chay,1,2 Dominic S Ting,1,2 SriniVas R Sadda3 1National Healthcare Group Eye Institute, Tan Tock Seng Hospital, Singapore; 2Fundus Image Reading Centre, National Healthcare Group Eye Institute, Singapore; 3Doheny Image Reading Center, Doheny Eye Institute, Los Angeles, CA, USACorrespondence: SriniVas R Sadda, Doheny Image Reading Center, Doheny Eye Institute, 3623, 1450 San Pablo Street, Los Angeles, CA, 90033, USA, Email sadda@usc.eduAbstract: Neovascular age-related macular degeneration (nAMD) is a common world-wide cause of visual loss. Intravitreal anti-vascular endothelial growth factor (anti-VEGF) agents are an effective means to treat nAMD and reduce its impact on vision compared to either sham treatment or photodynamic therapy. Currently, the approved anti-VEGF drugs include ranibizumab, aflibercept and brolucizumab. In addition, bevacizumab, used as an off-label drug, and has been shown to be effective in treating nAMD. While anti-VEGF agents are effective, its limitations include the requirement for frequent, often monthly injections, and the need for long-term treatment of nAMD. These present significant burdens on the healthcare system and on the patients. In addition, reviews of patients with nAMD treated with anti-VEGF have reported deterioration of vision over time with progression of geographic atrophy. These limitations are partly addressed by exploring different treatment regimens that reduce the frequency of treatments. Newer anti-VEGF drugs have been shown in Phase III clinical trials to have injection intervals as long as 12 or even 16 weeks for a proportion of patients. There is research on newer drugs that affect other pathways, such as the angiopoietin pathway, which may impact nAMD by extending the treatment interval and reducing the burden of treatment. Other measures include the use of sustained-release implants that release the drug regularly over a period of time, and can be refilled periodically, as well as hydrogel platforms that serve to release the drug. The use of biosimilars will also serve to reduce the cost of treatment for nAMD. A new frontier of gene therapy, primarily targeting genes involved in the transduction of retinal cells to produce anti-VEGF proteins intraocularly, also opens a new avenue of therapeutic approaches that can be used for treatment. This review paper will discuss both current treatment options and the newer treatments under development.Keywords: neovascular AMD, anti-VEGF, retina, gene therapy